Analysis on the atomization characteristics of aviation biofuel discharging from simplex swirl atomizer. (June 2015) - Sivakumar, D.; Vankeswaram, S.K.; Sakthikumar, R.; Raghunandan, B.N.
Highlights: Atomization of aviation biofuel discharging from simplex swirl atomizer studied. Measurements of spray angle, sheet breakup length and spray drop size are presented. Breakup data of biofuel sheet agree with predictions from film breakup model. Model-predicted drop size is higher than measured mean drop size of biofuel spray. Existing empirical correlation on mean drop size is checked for biofuel spray. Abstract: The atomization characteristics of aviation biofuel discharging from a simplex swirl atomizer into quiescent atmospheric air are studied. The aviation biofuel is a mixture of 90% commercially available camelina-derived biofuel and 10% VonSol-53 (aromatics). The experiments are conducted in a spray test facility at varying fuel flow rate conditions. The measured characteristics include atomizer flow number, spray cone angle, breakup length of liquid sheet, wavelength of undulations on liquid sheet, and spray droplet size. The characteristics of biofuel sheet breakup are deduced from the captured images of biofuel spray. The measurements of spray droplet size distribution are obtained using Spraytec. The experimentally measured characteristics of the biofuel sheet breakup are compared with the predictions obtained from the liquid film breakup model proposed by Senecal et al. (1999). The measurements of wavelength and breakup length of the biofuel sheet discharging from the simplex swirl atomizer agree well with the model predictions. The model-predicted droplet size for the biofuel spray is significantly higher than the experimentally measured Sauter mean diameter (SMD). The spray droplets formed from the liquid sheet breakup undergo secondary atomization until 35–45 mm from the atomizer exit and thereafter the SMD increases downstream due to the combined effect of fuel evaporation and droplet coalescence. A good comparison is observed between the experimentally measured SMD of the biofuel spray and the predictions obtained using the empirical correlation reported in literature for sprays discharging from simplex swirl atomizers.